2012
DOI: 10.1186/1475-2840-11-37
|View full text |Cite
|
Sign up to set email alerts
|

Vascular stem cells in diabetic complications: evidence for a role in the pathogenesis and the therapeutic promise

Abstract: Long standing diabetes leads to structural and functional alterations in both the micro- and the macro-vasculature. Vascular endothelial cells (ECs) are the primary target of the hyperglycemia-induced adverse effects. Vascular stem cells that give rise to endothelial progenitor cells (EPCs) and mesenchymal progenitor cells (MPCs) represent an attractive target for cell therapy for diabetic patients. A number of studies have reported EPC dysfunction as a novel participant in the culmination of the diabetic comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 82 publications
0
22
0
Order By: Relevance
“…Several studies have shown that exposure to high levels of glucose leads to a series of biochemical, structural and functional changes in mature vascular ECs and VSMCs, which can be summarized as follows [2,17]: 1) biochemical changes: accumulation of advanced glycation endproducts (AGEs); increased production of the procoagulant protein von Willebrand Factor (VWF); increased apoptosis, induced by increased oxidative stress; increase in intracellular Ca 2+ ; mitochondrial dysfunction; changes in intracellular metabolism of fatty acid; activation of the mitogen-activated protein kinase (MAPK) signaling pathways; and reduced phosphorylation/activation of protein kinase B (also known as Akt); 2) structural changes: increased production of extracellular matrix proteins, collagen and fibronectin, and of related enzymes (i.e., matrix metalloproteinases, MMPs); 3) functional changes: reduction in cell proliferation and migration; impairment of endothelium-dependent vasodilatation, linked to decreased production of vasodilators and increased production of vasoconstrictors; induction of ischemia and neo-angiogenesis [17]. In human retinal ECs, both the poly-ADP-ribose polymerase (PARP) and the nuclear factor-kappa B (NF-κB) signaling play central roles, as described below.…”
Section: Endothelial Cells and Vascular Smooth Muscle Cellsmentioning
confidence: 99%
“…Several studies have shown that exposure to high levels of glucose leads to a series of biochemical, structural and functional changes in mature vascular ECs and VSMCs, which can be summarized as follows [2,17]: 1) biochemical changes: accumulation of advanced glycation endproducts (AGEs); increased production of the procoagulant protein von Willebrand Factor (VWF); increased apoptosis, induced by increased oxidative stress; increase in intracellular Ca 2+ ; mitochondrial dysfunction; changes in intracellular metabolism of fatty acid; activation of the mitogen-activated protein kinase (MAPK) signaling pathways; and reduced phosphorylation/activation of protein kinase B (also known as Akt); 2) structural changes: increased production of extracellular matrix proteins, collagen and fibronectin, and of related enzymes (i.e., matrix metalloproteinases, MMPs); 3) functional changes: reduction in cell proliferation and migration; impairment of endothelium-dependent vasodilatation, linked to decreased production of vasodilators and increased production of vasoconstrictors; induction of ischemia and neo-angiogenesis [17]. In human retinal ECs, both the poly-ADP-ribose polymerase (PARP) and the nuclear factor-kappa B (NF-κB) signaling play central roles, as described below.…”
Section: Endothelial Cells and Vascular Smooth Muscle Cellsmentioning
confidence: 99%
“…6 These secondary complications stem from the effects of sustained levels of hyperglycemia on the vascular system of select organs. 7,8 Vascular endothelial cells lining blood vessel walls are the first to encounter high levels of circulating glucose. [7][8][9] Sustained uptake of glucose by vessel endothelial cells results in impaired cellular function, resulting in microvascular and macrovascular changes.…”
Section: Diabetes and Its Complicationsmentioning
confidence: 99%
“…7,8 Vascular endothelial cells lining blood vessel walls are the first to encounter high levels of circulating glucose. [7][8][9] Sustained uptake of glucose by vessel endothelial cells results in impaired cellular function, resulting in microvascular and macrovascular changes. 8,9 One of the earliest defects apparent in target organs of diabetic complications is a diminished capacity for vasodilation due to the unbalanced production of vasodilators and vasoconstrictors.…”
Section: Diabetes and Its Complicationsmentioning
confidence: 99%
See 2 more Smart Citations